The Impact of Dental Treatments on Blood Pressure Variations - Belisa Olmo González; Miguel ángel González-martín; José Manuel Olmo-villaseca; Anna Mañes-medina; Manuel Ribera-uribe (Cumhuriyet Dental Journal, 2019)
Objectives: The aim was to determine whether there are alterations in the fluctuations of systolic and diastolic blood pressure or the heart rate of normotensive versus hypertensive participants undergoing antihypertensive treatment during surgical and non-surgical dental treatments, regarding whether or not anaesthetics were used with a vasoconstrictor.Materials and methods: A prospective, observational, epidemiological study was conducted in a sample of 200 participants older than 65 years (100 normotensive and 100 hypertensive participants on antihypertensive treatment). Five periods for evaluation were established. Demographic information was obtained regarding whether or not anaesthetics were used (with or without a vasoconstrictor) and whether or not the participants underwent surgical treatment. The statistical analysis consisted of a doubly multivariate analysis of repeated measures for multiple dependent variables.Results: Significant differences were observed in the evolution of systolic blood pressure, with an initial increase in participants undergoing surgical treatment and those without a vasoconstrictor. On the other hand, systolic blood pressure decreased with non-surgical treatments, but it remained stable with the use of a vasoconstrictor. Diastolic blood pressure showed no interaction effect in participants undergoing surgical or non-surgical treatments; with the use of a vasoconstrictor, it initially decreased, while in the absence of a vasoconstrictor, it increased. Heart rate initially decreased in participants undergoing surgical and non-surgical treatments and was analogous whether or not a vasoconstrictor was used.Conclusions: During blood pressure monitoring, blood pressure variations occur, but there is no clinical repercussion in participants because once the treatment is completed, the initial values are recovered. Arterial hypertension is a pathology of high prevalence that tends to increase with age. The blood pressure response to surgical and non-surgical dental treatments and the effect of local anaesthetics is important because follow-up and blood pressure control in older patient cohorts can improve dental and clinical management.